Membongkar Potensi Investasi Tenaga Kerja dan Modal: Bagaimana Mempengaruhi Produktivitas di Sektor UMKM Indonesia? - Wicaksono, Baghas Budi; Hermawan, Aditiya; Evien (International Journal of Digital Entrepreneurship and Business, 2024)
This study investigates the impact of labor and capital investments on productivity within the Micro, Small, and Medium Enterprises (MSME) sector in Indonesia, utilizing data from 2016 to 2020. The analysis assesses MSME productivity and the proportion of MSME product exports relative to total exports. The findings reveal that labor and capital investments significantly and positively influence MSME productivity and export ratios. These results suggest that increased labor and capital investments in the MSME sector can enhance its contribution to the national economy. Consequently, policymakers should focus on strategies to boost investment and training in the MSME sector and facilitate access to export markets. This research contributes to the existing literature on MSME economics and economic growth, providing a foundation for further studies on additional factors influencing MSME performance, such as technology and innovation. The insights gained from this study not only guide policymakers but also support inclusive and sustainable economic development in Indonesia. By understanding the dynamics of labor and capital investment in the MSME sector, policymakers can formulate more effective policies to promote growth and resilience in this vital segment of the economy, ultimately fostering broader economic development and prosperity.